(untitled) - Price, James L; Mueller, Charles W (Cambridge, Mass., 1986)
Includes bibliography and index; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Organization -- Research; Sociometry; Tương tác xã hội -- Nghiên cứu -- Phép đo lường